Methods for estimating biomass in the tropical forest using remotely sensed data - Omar, Hamdan; Ismail, Mohd Hasmadi; Hamzah, Khali Aziz; Abu Hassan, Mohd Hakimi (Faculty of Forestry, Universiti Putra Malaysia, 2013)
In the past, remote sensing has been used for forest biomass estimation although with some uncertainties. Several methods have been developed to minimize these uncertainties. This study was carried out to determine the differences in biomass estimation between two approaches, ‘stratify and multiply’ (SM) and ‘direct remote sensing’ (DR). The 3666 ha lowland forest study area was located in the Dungun Timber Complex (DTC), Terengganu. Forest stratification was carried out using SPOT-5 satellite imagery acquired in February 2012. The study area was stratified into four strata, namely, natural virgin, logged-over between 20 to 30 years, 10 to 20 years and less than ten years. Twelve sampling plots were established. The SM approach was employed in areas where the average aboveground biomass (AGB) was calculated on plot basis for each strata. By using the same data from the sampling plots, the DR approach was applied to Phase Array Type L-Band SAR (PALSAR) data acquired in 2010. Total AGB of the study area was calculated based on pixel-size distribution. Results indicated that biomass estimated between these two methods differed.